Architecture of relict charcoal hearths in northwestern Connecticut, USA. Issue 4 (9th March 2017) - Raab, Thomas; Hirsch, Florian; Ouimet, William; Johnson, Katharine M.; Dethier, David; Raab, Alexandra
Abstract: Relict charcoal hearths are round or elliptical earthen platforms up to 11 m in diameter and a widespread feature of historical industry that supplied charcoal used in the production of iron in furnaces or smelters. The iron industry dominated Litchfield County, Connecticut, and surrounding areas in the northeast United States throughout the 19th century, peaking in ∼1850. The large number of charcoal hearths in this region is a relic of >150 years of widespread iron production. In this study, we describe the architecture and soil stratigraphy of 26 charcoal hearths in Litchfield County. This contribution aims to (1) compare soils that comprise the charcoal hearths with "natural" adjacent soils, (2) measure the thickness of topsoil developed upon the hearths, and (3) characterize the stratigraphy associated with these features. Results indicate that the black topsoils overlying the charcoal hearths contain residual charcoal and are on average 2.6 times thicker than adjacent Cambisols. Charcoal hearths display two or more black, charcoal‐rich strata separated by layers of reddish‐brown soil low in charcoal content indicating multiple episodes of use. We also find that many charcoal hearths have been stabilized with boulders on the downslope side during construction and repeated use. Overall, the results presented here provide significant information regarding the construction, use, and associated impacts of earthen platforms for charcoal production in the northeast United States, with further relevance to other areas where historical charcoal production occurred.